Electron transition pathways of graphene oxide quantum dots unraveled by emission wavelength dependent photoluminescence lifetime. Issue 32 (3rd April 2017) - Guo, Rongyan; Li, Tao; Shi, Shuie
Abstract : A comprehensive insight into the electron transition pathways of GOQDs is gained by the dependence of photoluminescence lifetime on emission. Abstract : The excitation wavelength dependent photoluminescence (PL) of graphene oxide quantum dots (GOQDs), which is frequently explained by size effects and radiative surface states, has drawn broad interest. In this work, the size of sp 2 carbon clusters embedded in the GOQDs are found to be 2.8–4.8 nm by transmission electron microscopy. The energy gap estimated by the effective-mass method matches approximately with the observed emission wavelength. It clearly shows that the photogenerated carriers are quantum confined in the sp 2 clusters. Moreover, the dependence of the PL lifetime on emission wavelength is close to a steady-state PL spectrum, which is different to that of semiconductor quantum dots, and suggests that the surface states significantly contribute to the long-wavelength emission.